Cracking the egg: molecular dynamics and evolutionary aspects of the transition from the fully grown oocyte to embryo - Evsikov, Alexei V. (Cold Spring Harbor Laboratory Press, 2006)
Fully grown oocytes (FGOs) contain all the necessary transcripts to activate molecular pathways underlying the oocyte-to-embryo transition (OET). To elucidate this critical period of development, an extensive survey of the FGO transcriptome was performed by analyzing 19,000 expressed sequence tags of the Mus musculus FGO cDNA library. Expression of 5400 genes and transposable elements is reported. For a majority of genes expressed in mouse FGOs, homologs transcribed in eggs of Xenopus laevis or Ciona intestinalis were found, pinpointing evolutionary conservation of most regulatory cascades underlying the OET in chordates. A large proportion of identified genes belongs to several gene families with oocyte-restricted expression, a likely result of lineage-specific genomic duplications. Gene loss by mutation and expression in female germline of retrotransposed genes specific to M. musculus is documented. These findings indicate rapid diversification of genes involved in female reproduction. Comparison of the FGO and two-cell embryo transcriptomes demarcated the processes important for oogenesis from those involved in OET and identified novel motifs in maternal mRNAs associated with transcript stability. Discovery of oocyte-specific eukaryotic translation initiation factor 4E distinguishes a novel system of translational regulation. These results implicate conserved pathways underlying transition from oogenesis to initiation of development and illustrate how genes acquire and lose reproductive functions during evolution, a potential mechanism for reproductive isolation.